Perovskite Solar Cells

By extending the sealing agent layer to cover the adhesive layer and substrate, the perovskite solar cells are protected from water ingress, improving durability and performance.

JP7623697B2Active Publication Date: 2025-01-29ENECOAT TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021178856
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-01
Publication Date
2025-01-29
Estimated Expiration
2041-11-01

AI Technical Summary

Technical Problem

Existing perovskite solar cells are vulnerable to water ingress, particularly through the interface between the transparent electrode and the barrier layer, which is not adequately addressed by existing sealing methods.

Method used

A sealing agent layer is applied to cover the entire adhesive layer and extend to the back of the substrate, with specific distances and configurations to prevent water entry, using a combination of adhesive layers and sealing films to create a robust barrier.

Benefits of technology

The solution effectively prevents water ingress, enhancing the durability and performance of perovskite solar cells by maintaining structural integrity and electrical efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623697000001
    Figure 0007623697000001
  • Figure 0007623697000002
    Figure 0007623697000002
  • Figure 0007623697000003
    Figure 0007623697000003
Patent Text Reader

Abstract

To provide a highly durable perovskite solar cell that prevents moisture and oxygen from entering a device.SOLUTION: A solar cell 1 includes a support 11 having a first side and a second side, a solar cell element 4 provided on the first surface of the support 11, an adhesive layer 13 covering the entire solar cell element 4, and a sealant layer 14 covering the entire adhesive layer 13, and the solar cell element 4 includes an electrode, a photoelectric conversion layer containing a perovskite compound, and a backside electrode in this order, and the sealant layer 14 includes a body portion 12 covering a portion of the adhesive layer 13 on the solar cell element 4, a first end region 15 that exists continuously with the body portion 12 and continues to the end of the first surface, and a second end region 17 that is continuous with the first end region 15 and extends to the second surface.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This invention relates to perovskite solar cells. [Background technology]

[0002] Perovskite solar cells are vulnerable to water, and creating a device structure that prevents water from entering the device is a challenge. WO2018 / 052032 describes a structure that seals the entire side of an organic insulating layer that covers the entire perovskite solar cell. Since water is likely to penetrate into this device through the organic insulating layer provided between the flexible substrate made of metal foil and the transparent electrode (40), the organic insulating layer is sealed with a barrier layer. However, the problem of water penetrating from the interface between the barrier layer and the transparent electrode (40) has not been resolved. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] WO2018 / 052032 publication Summary of the Invention [Problem to be solved by the invention]

[0004] One of the objects of the present invention is to provide a highly durable perovskite solar cell. [Means for solving the problem]

[0005] The above problems can basically be solved by providing a sealant layer that extends to the back surface of the substrate. The present invention relates to a solar cell 1. Solar cell 1 is A support 11 having a first surface and a second surface, A solar cell element 4 provided on a first surface of a support 11; An adhesive layer 13 that covers the entire solar cell element 4, A sealant layer 14 that covers the entire adhesive layer 13; Includes. If the distance from the end of the adhesive layer 13 to the end of the support 11 is d1, It is preferable that d1 is greater than or equal to 0.5 mm and less than or equal to 2 cm. The sealant layer 14 is preferably a layer constituted by one sealant film.

[0006] And the solar cell element 4 is Electrode 40, A photoelectric conversion layer 47 containing a perovskite compound; A back electrode 49, in this order.

[0007] The sealant layer 14 is A main body portion 12 that covers the adhesive layer 13 portion on the solar cell element 4, a first end region 15 that is continuous with the main body portion 12 and extends to an end of the first surface; The second end region 17 is continuous with the first end region 15 and continues to the second surface (exists on the second surface). If the distance from the end of the support 11 to the point where the end of the second end region 17 exists is d2, then d2 is preferably 0.2 mm or more and 1 cm or less.

[0008] The sealant layer 14 is A first partial sealant layer 14a including a main body portion 12; and a second partial sealant layer 14b covering the end of the first partial sealant layer 14a and constituting a region including the second end region 17. Effect of the Invention

[0009] According to the present invention, it is possible to provide a perovskite solar cell that can prevent water intrusion and has high durability. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a conceptual diagram showing an example of a cross-section of a solar cell. [Diagram 2] FIG. 2 is a conceptual diagram showing an example of a cross-section of a solar cell. [Diagram 3] FIG. 3 is a conceptual diagram showing an example of a cross-section of a solar cell. [Figure 4] FIG. 4 is a conceptual diagram showing an example of a cross-sectional view of a solar cell. [Diagram 5] FIG. 5 is a conceptual diagram showing an example of a cross-section of a solar cell. [Figure 6] FIG. 6 is a conceptual diagram showing an example of the structure of a perovskite solar cell element (normal type). [Figure 7] FIG. 7 is a conceptual diagram showing an example of the structure of a perovskite solar cell element (inverted type). [Figure 8] FIG. 8 is a conceptual diagram showing an example of the back surface (second surface) of a solar cell. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments for carrying out the present invention will be described with reference to the drawings. The present invention is not limited to the embodiments described below, and includes appropriate modifications of the embodiments described below within the scope obvious to those skilled in the art.

[0012] Hereinafter, the embodiments for carrying out the present invention will be described with reference to the drawings. The present invention is not limited to the embodiments described below, and includes appropriate modifications of the embodiments described below within the scope obvious to those skilled in the art.

[0013] Solar Cell The first invention relates to a solar cell. Figs. 1 to 5 are conceptual diagrams showing cross sections of a solar cell. As shown in Figs. 1 to 5, this solar cell 1 has a first support 11, a (perovskite) solar cell element 4, an adhesive layer 13, and a sealant layer 14. The sealant layer 14 has a main body portion 12 of the sealant layer covering the adhesive layer 13 on the solar cell element 4, a first end region 15, and a second end region 17. It is preferable that the main body portion of the sealant layer and each end region are continuously connected.

[0014] The example of FIG. 1 will be described. In this example, the adhesive layer 13 is a single layer. The adhesive layer 13 covers the solar cell element 4 and extends beyond the end of the solar cell element 4 on the first surface of the support 11. In this way, the adhesive layer 13 seals the solar cell element 4. The sealant layer 14 covers the entire adhesive layer 13. The sealant layer 14 extends not only to the first surface of the support but also to the second surface (rear surface). In this example, the sealant layer 14 is composed of a single film.

[0015] The example of Fig. 2 will be described. In this example, the sealant layer 14 includes a first partial sealant layer 14a and a second partial sealant layer 14b. The first partial sealant layer 14a is a layer that constitutes a portion of the sealant layer 14 that includes the main body portion 12. The second partial sealant layer 14b covers an end portion 18 of the first partial sealant layer 14a, and constitutes a region that includes a second end portion region 17. In this example, an end portion region 18, which will be described later, is present at the end portion of the first partial sealant layer 14a.

[0016] The example of FIG. 3 will be described. In this example, the adhesive layer 13 (first adhesive layer 13a) covers the solar cell element 4. The first partial sealant layer 14a is present so as to cover the upper region of the first adhesive layer 13a (and the solar cell element 4). In this example, the first partial sealant layer 14a covers the side surface of the first adhesive layer 13a and the solar cell element 4. In this way, the first partial sealant layer 14a functions as a sealant. Meanwhile, the second adhesive layer 13b bonds the first partial sealant layer 14a and the second partial sealant layer 14b, and also bonds the surface portion of the support 11 (where the first partial sealant layer 14a does not exist) to the second partial sealant layer 14b. The end of the second adhesive layer 13b and the end of the second partial sealant layer 14b on the back surface (second surface) of the support 11 may be in the same position. Either the end of the second adhesive layer 13b or the end of the second partial sealant layer 14b on the back surface (second surface) of the support 11 may be present first. In any case, it is preferable that either or both of the end of the second adhesive layer 13b and the end of the second partial sealant layer 14b on the back surface (second surface) of the support 11 are treated in the same manner as the end region 18 described later and are in the same condition.

[0017] The example of Fig. 4 will be described. This example differs from the example of Fig. 3 in that the first partial sealant layer 14a does not cover the first adhesive layer 13a and the side surface of the solar cell element 4. Each element will be described below.

[0018] The example of Fig. 5 will be described. In this example, the adhesive layer extends to the rear surface (second surface) of the support 11 in the example of Fig. 1.

[0019] Support 11 As the support 11, a known substrate for an organic solar cell or an organic EL element can be appropriately used. Examples of the substrate include glass, a plastic plate, a plastic film, and an inorganic crystal. In addition, a substrate having at least one film of a metal film, a semiconductor film, a conductive film, and an insulating film formed on a part or all of the surface of the substrate can also be preferably used. In particular, in order to reduce the thickness and weight, it is preferable that the support is a flexible substrate.

[0020] Solar cell element 4 The solar cell element means an element having a function of generating electricity by receiving light such as sunlight. The solar cell element is preferably one having a shape in which a perovskite layer (light absorption layer / photoelectric conversion layer) is sandwiched between an electron transport layer and a hole transport layer. The perovskite layer is preferably a perovskite layer made of an organic-inorganic hybrid compound. As shown in FIG. 6, the solar cell element 4 may have a normal structure in which an electron transport layer 46, a perovskite layer 47, a hole transport layer 48, and a back electrode 49 are formed from the transparent electrode 40 side. Also, as shown in FIG. 7, the solar cell element 4 may have either an inverted structure in which a hole transport layer 48, a perovskite layer 47, an electron transport layer 46, and a back electrode 49 are formed from the transparent electrode 40 side.

[0021] electrode 40 The electrode is preferably a transparent electrode for transmitting light. The transparent electrode is a support for the electron transport layer and is a layer having a function of extracting electrons from the perovskite layer (light absorbing layer / photoelectric conversion layer). The electrode is formed on the support 11. The transparent electrode is formed from a conductor, and specific examples include a tin-doped indium oxide (ITO) film, an impurity-doped indium oxide (In2O3) film, an impurity-doped zinc oxide (ZnO) film, a fluorine-doped tin dioxide (FTO) film, a laminated film obtained by laminating these, gold, silver, copper, aluminum, tungsten, titanium, chromium, nickel, cobalt, etc. These may be used alone or in a mixture of two or more types, and may be a single layer or a laminate. These films may function as, for example, a diffusion prevention layer. The thickness of these electrodes is not particularly limited, and is usually preferably adjusted so that the sheet resistance is 5 to 15 Ω / □ (per unit area). The electrodes can be obtained by a known film formation method depending on the material to be formed. These electrodes may be in the form of a film or a lattice such as a mesh. A known method is used for forming electrodes on a support, and vacuum film formation such as vacuum deposition or sputtering is preferred. Transparent electrodes may be patterned, and examples of such methods include a method of immersing in a laser or etching solution, and a method of patterning using a mask during vacuum film formation. Any method may be used in the present invention.

[0022] Electron transport layer 46 The electron transport layer 46 is preferably an electron transporting semiconductor, and examples of the semiconductor include oxides of titanium, tin, zinc, iron, tungsten, zirconium, indium, cerium, yttrium, aluminum, magnesium, vanadium, and niobium, and metal chalcogenides such as cadmium, zinc, lead, silver, antimony, and bismuth sulfides, cadmium and lead selenides, and cadmium telluride. Among these, oxides are particularly preferred. Among these, zinc oxide, tin oxide, and titanium oxide are particularly preferred. The electron transport layer may be a single layer or a multilayer, and in the case of a multilayer, it may be a porous shape in which semiconductor fine particles with different particle sizes are applied in multiple layers. In the case of a porous shape, the particle size of the semiconductor fine particles is preferably 3 to 100 nm, and more preferably 5 to 70 nm. The film thickness is preferably 5 to 1000 nm, and more preferably 10 to 500 nm.

[0023] The method for forming the electron transport layer is not particularly limited, and may be any of vacuum film formation such as sputtering or ion plating, or wet film formation such as sol-gel.

[0024] Hole transport layer 48 The hole transport layer 48 is a layer having a function of transporting charges. For example, a conductor, a semiconductor, an organic hole transport material, etc. can be used for the hole transport layer. The material can function as a hole transport material that receives holes from the perovskite layer (light absorption layer) and transports the holes. Examples of the conductor and semiconductor include compound semiconductors containing monovalent copper such as CuI, CuInSe2, and CuS; and compounds containing metals other than copper such as GaP, NiO, CoO, FeO, Bi2O3, MoO2, and Cr2O3. Among them, from the viewpoint of more efficiently receiving only holes and obtaining higher hole mobility, a semiconductor containing monovalent copper is preferable, and CuI is more preferable. Examples of organic hole transport materials include polythiophene derivatives such as poly-3-hexylthiophene (P3HT) and polyethylenedioxythiophene (PEDOT); fluorene derivatives such as 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)-9,9'-spirobifluorene (Spiro-OMeTAD); carbazole derivatives such as polyvinylcarbazole; triphenylamine derivatives such as poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA); diphenylamine derivatives; polysilane derivatives; polyaniline derivatives, etc. Among these, triphenylamine derivatives and fluorene derivatives are preferred, and PTAA and Spiro-OMeTAD are more preferred, from the viewpoint of more efficiently receiving only holes and obtaining higher hole mobility.

[0025] In order to further improve the hole transport properties, the hole transport layer may contain an oxidizing agent such as lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), silver bis(trifluoromethylsulfonyl)imide, trifluoromethylsulfonyloxysilver, NOSbF6, SbCl5, SbF5, tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tri[bis(trifluoromethane)sulfonimide]. In addition, the hole transport layer may contain a basic compound such as t-butylpyridine (TBP), 2-picoline, 2,6-lutidine. The content of the oxidizing agent and the basic compound may be the amount that has been conventionally used. The thickness of the hole transport layer is preferably, for example, 50 to 800 nm, more preferably 100 to 600 nm, from the viewpoint of more efficiently receiving only holes and obtaining higher hole mobility. The method of forming the hole transport layer is not particularly limited, and may be performed according to a known method. For example, wet film formation methods such as a dipping method, a spraying method, a spin coating method, and a blade coating method, and vacuum film formation methods such as a sputtering method can be mentioned.

[0026] Perovskite layer (light absorption layer / photoelectric conversion layer) 47 The perovskite layer (light absorbing layer / photoelectric conversion layer) 47 is a layer that absorbs light and performs photoelectric conversion by transferring excited electrons and holes. The perovskite compound in the present invention is preferably a composite material of an organic compound and an inorganic compound. The perovskite compound preferably exhibits a layered perovskite structure in which layers made of metal halide and layers in which organic cation molecules are arranged are alternately stacked, and is represented by the following general formula (1). XαYβMγ · · General formula (1) In the above general formula (1), X represents a halogen atom, Y represents an alkylamine compound, M represents at least one metal ion selected from lead, tin, indium, antimony, and bismuth, the ratio of α:β:γ is 3:1:1, and β and γ represent integers greater than 1. X may be a halogen atom such as chlorine, bromine, or iodine, which may be used alone or as a mixture. Y may be an alkylamine compound such as methylamine, ethylamine, n-butylamine, or formamidine.

[0027] Furthermore, the flatness of the perovskite layer is preferably such that the height difference is 50 nm or less (-25 nm to +25 nm) and more preferably 40 nm or less (-20 nm to +20 nm) in a range of 500 nm x 500 nm in the horizontal direction of the surface as measured by a scanning electron microscope. This makes it easier to balance the light absorption efficiency and the exciton diffusion length, and can further improve the absorption efficiency of light reflected by the electrode.

[0028] Examples of methods for forming a perovskite layer include a one-step precipitation method in which a solution in which metal halides and alkylamine halides are dissolved or dispersed in a solvent is applied to the electron transport layer or hole transport layer and dried, or a two-step precipitation method in which a solvent in which metal halides are dissolved or dispersed is applied to the electron transport layer or hole transport layer, dried, and then immersed in a solution in which alkylamine halides are dissolved in the solvent to form a perovskite layer. In the one-step precipitation method, it is also possible to promote crystallization all at once by adding a solvent that does not dissolve the perovskite compound before complete application.

[0029] After forming the perovskite compound layer, a solution of a halogenated amine compound may be applied onto the perovskite layer. Examples of the halogenated amine compound used in this case include phenylethylamine bromide, phenylethylamine iodide, n-hexyltrimethylamine bromide, n-octadecylamine iodide, 5-ammonium valerate iodide, etc., and these may be used alone or in combination of two or more kinds.

[0030] Back electrode 49 Examples of the back electrode 49 include metals such as platinum, gold, silver, copper, aluminum, rhodium, nickel, cobalt, iron, palladium, and indium; carbon-based compounds such as graphite, graphene, and carbon nanotubes; conductive metal oxides such as ITO, indium-doped zinc oxide (IZO), and antimony-doped tin oxide (ATO); and conductive polymers such as polythiophene or polyaniline, which may be used alone or in combination of two or more. The back electrode may be a transparent electrode. The thickness of the back electrode is not particularly limited, and may be a single film of the above-mentioned materials or a mixture or laminate of two or more of them. The back electrode can be formed by applying, laminating, vacuum deposition, CVD, laminating, or other methods on the hole transport layer depending on the type of material used and the type of hole transport layer.

[0031] adhesive layer 13 The adhesive layer is a layer that covers the solar cell element 4. The adhesive layer may cover the entire solar cell element or may cover a part of the solar cell element. The adhesive layer is a layer that is disposed between the support and the sealant layer (main body). The adhesive layer is used to bond the support and the sealant layer, as well as to bond the solar cell element on the support and the sealant layer. However, when the adhesive layer covers the entire solar cell element, it also has the function of sealing the solar cell element. There are no particular restrictions on the material of the adhesive, and it can be selected appropriately depending on the purpose. For example, hardened acrylic resin or epoxy resin can be used. As the cured acrylic resin, any known material can be used so long as it is a cured monomer or oligomer having an acrylic group in the molecule, and as the cured epoxy resin, any known material can be used so long as it is a cured monomer or oligomer having an epoxy group in the molecule.

[0032] Epoxy resins include water-dispersed, solvent-free, solid, heat-cured, mixed with curing agent, and ultraviolet cured. Of these, heat-cured and ultraviolet cured are preferred, and ultraviolet cured is more preferred. Even if the resin is ultraviolet cured, it is possible to heat it, and it is preferred to heat it even after ultraviolet curing. Specific examples of epoxy resins include bisphenol A type, bisphenol F type, novolac type, cyclic aliphatic type, long-chain aliphatic type, glycidylamine type, glycidyl ether type, and glycidyl ester type, which may be used alone or in combination of two or more types. In addition, it is preferred to mix a curing agent or various additives into the epoxy resin as necessary. Epoxy resin compositions that are already on the market can be used in the present invention. Among these, there are also epoxy resin compositions that have been developed and are commercially available for use in solar cells and organic EL elements, which can be used particularly effectively in the present invention. Commercially available epoxy resin compositions include, for example, TB3118, TB3114, TB3124, TB3125F (manufactured by ThreeBond Co., Ltd.), World Rock 5910, World Rock 5920, World Rock 8723 (manufactured by Kyoritsu Chemical Industries Co., Ltd.), and WB90US(P) (manufactured by MORESCO Corporation).

[0033] The curing agent is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include amine-based, acid anhydride-based, polyamide-based, and other curing agents. Examples of amine-based curing agents include aliphatic polyamines such as diethylenetriamine and triethylenetetramine, and aromatic polyamines such as metaphenylenediamine, diaminodiphenylmethane, and diaminodiphenylsulfone. Examples of acid anhydride-based curing agents include phthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, pyromellitic anhydride, het acid anhydride, and dodecenyl succinic anhydride. Examples of other curing agents include imidazoles and polymercaptan. These may be used alone or in combination of two or more types.

[0034] The additives are not particularly limited and can be appropriately selected according to the purpose. For example, fillers, gap agents, polymerization initiators, desiccants (moisture absorbents), hardening accelerators, coupling agents, flexibilizers, colorants, flame retardant assistants, antioxidants, organic solvents, etc. are listed. Among these, fillers, gap agents, hardening accelerators, polymerization initiators, and desiccants (moisture absorbents) are preferred, and fillers and polymerization initiators are more preferred. By including a filler as an additive, it is possible to suppress the intrusion of moisture and oxygen, and further to obtain effects such as reducing the volumetric shrinkage during hardening, reducing the amount of outgassing during hardening or heating, improving mechanical strength, and controlling thermal conductivity and fluidity. Therefore, including a filler as an additive is very effective in maintaining stable output in various environments. The additive may be added to the sealant layer or the end region.

[0035] Furthermore, with regard to the output characteristics and durability of solar cell elements, the effects of not only the intrusion of moisture and oxygen, but also the outgassing that occurs when the sealing material hardens or is heated cannot be ignored. In particular, the effect of outgassing that occurs when heated has a significant effect on output characteristics when stored in a high-temperature environment. By incorporating a filler, gap agent, or desiccant into the adhesive layer or sealant layer, these themselves can suppress the intrusion of moisture and oxygen, and by reducing the amount of adhesive or sealant used, the effect of reducing outgassing can be obtained. Incorporating a filler, gap agent, or desiccant into the adhesive layer or sealant layer is effective not only during hardening, but also when storing solar cell elements in a high-temperature environment.

[0036] The filler is not particularly limited and can be appropriately selected according to the purpose. For example, inorganic fillers such as crystalline or amorphous silica, silicate minerals such as talc, alumina, aluminum nitride, silicon nitride, calcium silicate, calcium carbonate, etc. are listed. Among these, hydrotalcite is particularly preferable. These may be used alone or in combination of two or more kinds.

[0037] The average primary particle size of the filler is preferably 0.1 μm to 10 μm, more preferably 1 μm to 5 μm. If the average primary particle size of the filler is within the above preferred range, the effect of suppressing the intrusion of moisture and oxygen can be sufficiently obtained, the viscosity becomes appropriate, the adhesion to the substrate and the defoaming property are improved, and it is also effective for controlling the width of the sealant layer and workability.

[0038] The content of the filler is preferably 10 parts by mass or more and 90 parts by mass or less, and more preferably 20 parts by mass or more and 70 parts by mass or less, relative to the total (100 parts by mass) of the adhesive layer etc. When the content of the filler is within the above preferred range, the effect of suppressing the intrusion of moisture and oxygen is sufficiently obtained, the viscosity is appropriate, and the adhesion and workability are also good.

[0039] The gap agent is also called a gap control agent or spacer agent. By including a gap agent as an additive, it becomes possible to control the gap in the sealant layer. For example, when an adhesive layer is applied on a first substrate or a first electrode, and a second substrate is placed on top of the adhesive layer to perform sealing, the gap in the sealant layer is aligned to the size of the gap agent because the adhesive layer or sealant layer contains a gap agent, so that the gap in the sealant layer can be easily controlled. There are no particular limitations on the gap agent, so long as it is granular, has a uniform particle size, and has high solvent resistance and heat resistance, and can be appropriately selected according to the purpose. As the gap agent, one that has high affinity with epoxy resin and has a spherical particle shape is preferable. Specifically, glass beads, silica fine particles, organic resin fine particles, etc. are preferable. These may be used alone or in combination of two or more types. The particle size of the gap agent can be selected according to the gap to be set in the end region of the sealant layer, but is preferably 1 μm or more and 100 μm or less, and more preferably 5 μm or more and 50 μm or less.

[0040] There are no particular limitations on the polymerization initiator as long as it uses heat or light to initiate polymerization, and it can be appropriately selected depending on the purpose. Examples of the polymerization initiator include thermal polymerization initiators and photopolymerization initiators. Thermal polymerization initiators are compounds that generate active species such as radicals and cations when heated, and include azo compounds such as 2,2'-azobisbutyronitrile (AIBN) and peroxides such as benzoyl peroxide (BPO). Benzene sulfonate esters and alkylsulfonium salts are used as thermal cationic polymerization initiators. On the other hand, in the case of epoxy resin, a photocationic polymerization initiator is preferably used as the photopolymerization initiator. When a photocationic polymerization initiator is mixed with epoxy resin and exposed to light, the photocationic polymerization initiator decomposes to generate acid, which then causes the epoxy resin to polymerize and the curing reaction to proceed. A photocationic polymerization initiator has the effects of causing little volumetric shrinkage during curing, not being inhibited by oxygen, and having high storage stability.

[0041] Examples of photo-cationic polymerization initiators include aromatic diazonium salts, aromatic iodonium salts, aromatic sulfonium salts, methacerone compounds, and silanol aluminum complexes. In addition, photo-acid generators that have the function of generating acid by irradiation with light can also be used as polymerization initiators. Photo-acid generators act as acids that initiate cationic polymerization, and include onium salts such as ionic sulfonium salts and iodonium salts that consist of a cationic portion and an anionic portion. These may be used alone or in combination of two or more types.

[0042] The amount of polymerization initiator added may vary depending on the material used, but is preferably 0.5 parts by mass to 10 parts by mass, more preferably 1 part by mass to 5 parts by mass, relative to the entire sealing member (100 parts by mass). By adding an amount within the above preferred range, curing proceeds properly, the amount of uncured material remaining can be reduced, and excessive outgassing can be prevented.

[0043] A desiccant (also known as a moisture absorbent) is a material that has the ability to physically or chemically adsorb and absorb moisture. By incorporating it into a sealing material, it is possible to further increase moisture resistance and reduce the effects of outgassing. The desiccant is not particularly limited and can be appropriately selected depending on the purpose, but particulate desiccants are preferable, and examples of such desiccants include inorganic water-absorbing materials such as calcium oxide, barium oxide, magnesium oxide, magnesium sulfate, sodium sulfate, calcium chloride, silica gel, molecular sieves, and zeolite. Among these, zeolite, which has a high moisture absorption capacity, is preferable. These may be used alone or in combination of two or more types.

[0044] A curing accelerator (also called a curing catalyst) is a material that accelerates the curing rate and is mainly used for thermosetting epoxy resins. The curing accelerator is not particularly limited and can be appropriately selected according to the purpose. For example, tertiary amines or tertiary amine salts such as DBU (1,8-diazabicyclo(5,4,0)-undecene-7) or DBN (1,5-diazabicyclo(4,3,0)-nonene-5), imidazoles such as 1-cyanoethyl-2-ethyl-4-methylimidazole or 2-ethyl-4-methylimidazole, phosphines or phosphonium salts such as triphenylphosphine or tetraphenylphosphonium tetraphenylborate, etc. can be used alone or in combination of two or more kinds.

[0045] The coupling agent is not particularly limited as long as it is a material that has the effect of enhancing molecular bonding strength, and can be appropriately selected according to the purpose, for example, silane coupling agents, etc. Specific examples include silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, N-(2-aminoethyl)3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)3-aminopropylmethyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, vinyltrimethoxysilane, N-(2-(vinylbenzylamino)ethyl)3-aminopropyltrimethoxysilane hydrochloride, and 3-methacryloxypropyltrimethoxysilane. These may be used alone or in combination of two or more kinds.

[0046] In the present invention, a sheet-like adhesive can be used. A sheet-like adhesive is a sheet on which a resin layer has been formed in advance, and the sheet can be made of glass or a film with high gas barrier properties. The sheet may also be made of resin only. The sheet-like adhesive can also be attached onto a sealing film. It is also possible to create a structure with a hollow portion on the sealing film and then attach it to the device.

[0047] For example, in the solar cell shown in FIG. 1 or FIG. 2, the distance (first distance) between the end of the solar cell element and the end of the adhesive layer is preferably 0.5 mm or more and 2 cm or less. The end of the solar cell element means the outer part of the solar cell element. For example, when the solar cell element is rectangular, the part on the edge of the rectangle constitutes the end of the solar cell element. The end of the adhesive layer means the outermost edge of the adhesive layer. This first end-to-end distance means the closest one between the edge of the solar cell element and the end of the adhesive layer (the edge on the opposite side to the solar cell element). The first distance is preferably 1 mm or more, and more preferably 2 mm or more. However, the first distance may be appropriately adjusted depending on the size of the solar cell element. When the solar cell element is rectangular and the length of the long side is l, the first distance may be 0.01 l or more and 0.5 l or less, or may be 0.05 l or more and 0.2 l or less.

[0048] Next, if the distance from the end of the adhesive layer 13 to the end of the support 11 is d1, d1 is preferably 0.5 mm or more and 2 cm or less, preferably 1 mm or more, and may be 2 mm or more. d1 may be 0.01 l or more and 0.5 l or less, or may be 0.05 l or more and 0.2 l or less. When there are multiple adhesive layers, it is preferable that d1 is the above value for any one or more of the adhesive layers. Also, when the adhesive layer 13 exists only on the front surface (first surface) of the support 11, the distance from the end of the area where the adhesive layer 13 exists to the end of the support 11 is d1. On the other hand, when the adhesive layer 13 exists up to the back surface (second surface) of the support 11 as in the example shown in FIG. 5, the width (length) of the area where the adhesive layer 13 exists on the back surface is d1.

[0049] Sealant layer (main body) 14 The sealant layer (main body) is formed to cover the adhesive layer and means a layer for preventing water and the like from entering the solar cell element. In order to distinguish it from the end region, it is also referred to as the sealant layer or the main body in this specification. The sealant layer is preferably one that covers the solar cell element and the adhesive layer. The sealant layer is disposed, for example, facing the support so as to sandwich the solar cell element including the photoelectric conversion layer and the electrode. The sealant layer may be composed of a sealant film. There are no particular limitations on the shape, structure, size, and type (material) of the sealant layer, and they can be appropriately selected according to the purpose. The sealant layer may be in the form of a thin film or a film.

[0050] The material constituting the sealant layer may be the same as the material of the adhesive layer. Other examples of the material of the sealant layer include a resin substrate having a barrier layer formed on the surface thereof to prevent the passage of moisture and oxygen, and the barrier layer may be formed on one or both sides of the substrate. In the latter case, the material of the resin substrate is not particularly limited, and examples thereof include polyolefin-based resins such as homopolymers or copolymers of ethylene, propylene, butene, etc.; amorphous polyolefin-based resins such as cyclic polyolefins; polyester-based resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); polyamide-based resins such as nylon 6, nylon 66, nylon 12, and copolymer nylon; ethylene-vinyl acetate copolymer partial hydrolyzate (EVOH), polyimide-based resins, polyetherimide-based resins, polysulfone-based resins, polyethersulfone-based resins, polyetheretherketone-based resins, polycarbonate-based resins, polyvinyl butyral-based resins, polyarylate-based resins, fluororesins, acrylic resins, and biodegradable resins. Among these, polyester resins are preferred from the viewpoint of film properties such as heat resistance and transparency, and polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) are particularly preferred. The resin substrate may be made of one type of resin material or two or more types of resin materials.

[0051] The resin substrate may contain other materials such as inorganic fillers to improve the durability of the solar cell module. There are no particular limitations on the inorganic fillers, but examples of the inorganic fillers include silica, mica, talc, clay, bentonite, montmorillonite, kaolinite, wollastonite, calcium carbonate, titanium oxide, alumina, barium sulfate, potassium titanate, and glass fiber. The inorganic fillers mixed into the resin substrate may be one type or two or more types.

[0052] The barrier layer is composed primarily of metal oxides, metals, mixtures formed from polymers and metal alkoxides, and examples of such materials include aluminum oxide, silicon oxide, and aluminum. Examples of polymers include polyvinyl alcohol, polyvinylpyrrolidone, and methyl cellulose. Examples of metal alkoxides include tetraethoxysilane, triisopropoxyaluminum, 3-glycidoxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, and 3-isocyanatopropyltriethoxysilane.

[0053] The barrier layer may be transparent or opaque. The barrier layer may be a single layer or a laminated structure of multiple layers made of the above materials. The barrier layer may be formed by a known method, such as vacuum film formation such as sputtering, dipping, roll coating, screen printing, spraying, and gravure printing. The thickness of the main body of the sealant layer may be within the range generally used in this technology. For example, it may be appropriately set within the range of 0.05 to 1 mm.

[0054] The sealant layer preferably covers the entire adhesive layer, and is preferably larger than the adhesive layer to prevent the intrusion of water and oxygen. In the example of FIG. 2, the distance (second distance) between the end of the adhesive layer 13 and the end region of the first sealant layer 14a is preferably 0.2 mm or more and 1 cm or less. The end of the adhesive layer is as described above. The end region of the sealant layer means the high-density region that exists at the outermost edge of the sealant layer. The distance between the end of the adhesive layer and the end region of the sealant layer means the distance at which the distance between the end of the adhesive layer and the end region of the sealant layer is the smallest. The second distance is preferably 0.5 mm or more, more preferably 1 mm or more. In addition, although the upper limit differs depending on the size and use of the solar cell, if it is too large, the solar cell (device) itself will become too large, or parts other than the solar cell element will become too large and will be wasted, so 1 cm or less is preferable, 5 mm or less is preferable, and 4 mm or less is more preferable.

[0055] End area 18 The end region 18 means, for example, a region provided in the end region of the sealant layer 14, the first partial sealant layer 14a, or the second partial sealant layer 14b, and having a higher density than the main body of the sealant layer. The end region is provided to more firmly insulate the outer periphery of the sealant layer from water and oxygen. It is preferable that the end region is formed integrally with the sealant layer. The shape of the end region is not particularly limited. It is preferable that the shape of the end region is a shape obtained by compressing the main body.

[0056] The width of the end region (first width) is preferably 0.5 mm or more and 1.5 cm or less. The first width is preferably 1 mm or more, more preferably 1.5 mm or more, so as to prevent the intrusion of moisture and oxygen and to adhere closely to the sealant body so as not to peel off. Moreover, since this can cause the solar cell (device) to become too large, or parts other than the solar cell element to become too large and become wasteful, the width is preferably 1.5 cm or less, more preferably 1 cm or less, and more preferably 5 mm or less.

[0057] Furthermore, it is preferable that the end region is made opaque so that it can be easily distinguished from the sealant layer (main body). There is no particular limitation on the method of making the end region opaque in this way, but examples include a method of including a filler that can be used in the adhesive layer or sealant layer (main body) or including a known pigment or dye. The cross-sectional shape of the end region may be a flat shape parallel to the support. The thickness of the end region may be less than or equal to the thickness of the sealant layer.

[0058] The end region can be formed, for example, by applying pressure to the end of the sealant layer (a portion other than the main body portion and located on the outer periphery) to crush the sealant layer. The pressure applied to the end region of the sealant layer is preferably 0.1 MPa to 10 MPa, and may be 1 MPa to 5 MPa. In the end pressurizing step, the sealant layer is preferably compressed so that the thickness of the end region is 55% to 90% of the thickness before the end pressurizing step, and may be compressed so that the thickness is 60% to 80%.

[0059] If the distance from the end of the support 11 to the point where the end of the second end region 17 exists is d2, d2 is preferably 0.2 mm or more and 1 cm or less, preferably 1 mm or more, and may be 2 mm or more. d1 may be 0.01 l or more and 0.5 l or less, or may be 0.05 l or more and 0.2 l or less. d2 can also be said to be the width (width of the folded part) of the sealant layer 14 on the back surface (second surface) of the support 11. This width may be the same or different between the part on the long side of the support and the part on the short side of the support. In the example of FIG. 8, this width (d2) is the same between the part on the long side of the support and the part on the short side of the support.

[0060] FIG. 8 is a conceptual diagram showing an example of the back surface (second surface) of a solar cell. FIG. 8(a) shows an example in which a sealant layer present on the short side of a support is placed on top of a sealant layer present on the long side of the support and then pressed together. FIG. 8(b) shows an example in which a sealant layer present on the long side of a support is placed on top of a sealant layer present on the short side of the support and then pressed together. FIG. 8(c) shows an example in which the sealant layer is processed so that the overlapping area is small (preferably, so that there is no overlapping area) when the sealant layer present on the long side of the support and the sealant layer present on the short side of the support are placed on top of each other, and then the sealant layer is folded back on the back surface (second surface) of the support.

[0061] Solar cells are publicly known. Thus, a person skilled in the art can manufacture the solar cells described in this specification by appropriately adopting publicly known methods while referring to the above description. In addition, the method of using solar cells is publicly known. EXAMPLES

[0062] A glass substrate with ITO (25mm x 24.5mm, Geomatec) was ultrasonically cleaned for 15 minutes each with 2-propanol, acetone, Semicoclean 56 (cleaning solution for displays, product name, product of Furuuchi Chemical Co., Ltd.), water, and 2-propanol, in that order, and then plasma treated. Next, 300μL of a water-soluble SnO2 colloidal solution (a 15% SnO2 colloidal solution diluted 1:1 with pure water and passed through a PTFE filter) was dropped onto the substrate as an electron transport layer, and a film was formed using spin coating (3000 rpm, 20 seconds), and then heated and dried at 150℃ for 30 minutes. The substrate was moved to a glove box, and a perovskite precursor solution was prepared by dissolving CsI, MABr (methylammonium bromide, CH3N·HBr), PbBr2, PbI2, and FAI (formamidine hydroiodide, CH4N2·HI) in a mixed solvent of DMF and DMSO (volume ratio 10:3) to prepare a solution with a concentration of 1.05 M. After filtering this solution using a PTFE filter, 190 μL was applied to the above substrate on which the electron transport layer was formed, spin-coated (1000 rpm with a slope of 1 s, 10 s, then 3000 rpm with a slope of 5 s, 20 s), during which 300 μL of chlorobenzene was dropped. The obtained device was then heated at 150 °C for 10 min. Next, a solution of 72.3 mg of hole transport material Spiro-OMeTAD, 13.5 mg of [tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III) tris(bis(trifluoromethylsulfonyl)imide)] (FK209, Fujifilm Wako Pure Chemical Industries, Ltd.), 28.8 μL of 4-t-butylpyridine, and 9.1 mg of LiTFSI in 1 mL of chlorobenzene was stirred for 30 minutes, filtered through a PTFE filter, and 90 μL was spin-coated onto the perovskite layer (4000 rpm with a slope of 4 seconds, 30 seconds, then stopped at a slope of 4 seconds), and then dried by heating at 70 °C for 30 minutes. Finally, 80 nm of gold was formed by vacuum deposition to obtain a perovskite solar cell element.

[0063] As an adhesive, 1.0g of hydrotalcite and Epoch epoxy resin (E-01-001 base: 4.0g, hardener: 2.0g) were mixed and applied to the perovskite solar cell element using spin coating (1000 rpm, 120 seconds), and unnecessary parts were removed with acetone. Next, an aluminum oxide vapor-deposited PET film (product name: Barialox, Toray Industries, Inc.) cut to a size larger than the area to which the adhesive was applied was attached, and heated at 80°C for 1 hour.

[0064] The outer periphery of this large cut film was folded along the support to produce a solar cell device as shown in Figure 6A. At this time, d1 was 2.0 mm and d2 was 1.2 mm. The film was folded in the order shown in Figure 8(a), and the overlapping portion was placed on a hot plate and heated at 80°C for 1 hour. The solar cell device was placed in a solar simulator (Bunkokeiki Co., Ltd. SM-250PV, light intensity: 100 mW / cm 2 The solar cell characteristics were measured using the device. The results were an open circuit voltage of 1.08 V and a short circuit current density of 22.0 mA / cm. 2 A form factor of 0.74 and a conversion efficiency of 17.6% were obtained. Next, this solar cell device was placed in a constant temperature and humidity tester at 60℃ and 90% RH to carry out a durability test. After 500 hours, the retention rate of the initial characteristics was 93%. [Experimental Example 1]

[0065] A solar cell device was fabricated in the same manner as in Example 1, except that the outer periphery of the film in Example 1 was not folded, and the solar cell characteristics were evaluated. As a result, the open circuit voltage was 1.10 V, and the short circuit current density was 22.0 mA / cm 2 The results showed that the device had a form factor of 0.72 and a conversion efficiency of 17.4%, which were equivalent to those of Example 1. Next, a durability test was conducted in a constant temperature and humidity chamber in the same manner as in Example 1, and the retention rate after 500 hours was measured, resulting in a result of 42%, which made it clear that the device structure of the present invention has excellent durability. EXAMPLES

[0066] In Example 1, an adhesive layer (first layer) of the same size as the portion on which the perovskite solar cell element was formed was formed, and then the top of that was covered with a sealant layer (first layer), and an adhesive layer was formed again to cover the entire top of that with the same adhesive (second layer), and the top of that was then covered with a sealant layer the same as the first layer (second layer). The outer periphery of this second layer was subjected to thermocompression bonding in the same manner as in Example 1 to produce a solar cell device as shown in Fig. 3. As a result, d1 was 1.8 mm and d2 was 0.4 mm. The solar cell characteristics of this device were measured, revealing an open circuit voltage of 1.08 V and a short circuit current density of 22.1 mA / cm. 2 A form factor of 0.72 and a conversion efficiency of 17.2% were obtained. Next, a durability test was conducted in a constant temperature and humidity chamber in the same manner as in Example 1, and the retention rate after 500 hours was measured, resulting in 92%, which clearly demonstrated that the device structure of the present invention has excellent durability. EXAMPLES

[0067] On the perovskite solar cell element in Example 1, an adhesive layer (first layer) of the same size as the portion where the element was formed was formed, and a sealant layer (first layer) was formed on top of that, and then an adhesive layer was formed again to cover the entire top of that with the same adhesive (second layer), and then the top of that was covered with a sealant layer the same as the first layer (second layer). The outer periphery of this second layer film was subjected to thermocompression bonding in the same manner as in Example 1 to produce a solar cell device as shown in Fig. 4. As a result, d1 was 4.1 mm and d2 was 0.9 mm. The solar cell characteristics of this device were measured, revealing an open circuit voltage of 1.11 V and a short circuit current density of 22.2 mA / cm. 2 A form factor of 0.72 and a conversion efficiency of 17.7% were obtained. Next, a durability test was conducted in a constant temperature and humidity chamber in the same manner as in Example 1, and the retention rate after 500 hours was measured, resulting in 95%, which clearly demonstrated that the device structure of the present invention has excellent durability. [Experimental Example 2]

[0068] A solar cell device was fabricated in the same manner as in Example 2, except that pressure was not applied to the outer periphery of the film, and the solar cell characteristics were evaluated. As a result, the open circuit voltage was 1.09 V, and the short circuit current density was 22.0 mA / cm 2 The results showed that the device had a form factor of 0.72 and a conversion efficiency of 17.3%, which were equivalent to those of Example 2. Next, a durability test was conducted in a constant temperature and humidity chamber in the same manner as in Example 1, and the retention rate after 500 hours was measured, resulting in 51%, which made it clear that the device structure of the present invention has excellent durability. [Experimental Example 3]

[0069] A solar cell device was fabricated in the same manner as in Example 3, except that pressure was not applied to the outer periphery of the film, and the solar cell characteristics were evaluated. As a result, the open circuit voltage was 1.10 V, and the short circuit current density was 22.0 mA / cm 2 The results showed that the device had a form factor of 0.71 and a conversion efficiency of 17.2%, which were equivalent to those of Example 3. Next, a durability test was conducted in a constant temperature and humidity chamber in the same manner as in Example 1, and the retention rate after 500 hours was measured, resulting in a result of 48%, which made it clear that the device structure of the present invention has excellent durability.

Claims

1. A support (11) having a first surface and a second surface; A solar cell element (4) provided on the first surface of the support (11); An adhesive layer (13) that covers the entire solar cell element (4); A sealant layer (14) that covers the entire adhesive layer (13); Including, The solar cell element (4) is An electrode (40); A photoelectric conversion layer (47) containing a perovskite compound; a back electrode (49), in that order; The sealant layer (14) is A main body portion (12) that covers the adhesive layer (13) portion on the solar cell element (4); a first end region (15) that is continuous with the main body portion (12) and extends to an end of the first surface; and a second end region (17) that is continuous with the first end region (15) and extends to the second surface. A solar cell (1), comprising: The sealant layer (14) is A first partial sealant layer (14a) including the main body portion (12); a second partial sealant layer (14b) covering an end portion of the first partial sealant layer (14a) and constituting an area including the second end area (17); Solar cell.

2. The solar cell according to claim 1 , The distance from the end of the adhesive layer (13) to the end of the support (11) is d 1 Then, d 1 A solar cell having a size of 0.5 mm or more and 2 cm or less.

3. The solar cell according to claim 1 , The distance from the end of the support (11) to the point where the end of the second end region (17) is located is defined as d 2 Then, d 2 A solar cell having a size of 0.2 mm or more and 1 cm or less.

4. The solar cell according to claim 1 , The distance from the end of the adhesive layer (13) to the end of the support (11) is d 1 year, The distance from the end of the support (11) to the point where the end of the second end region (17) is located is defined as d 2 Then, d 1 / d 2 A solar cell, wherein the coefficient of resistance is greater than or equal to 0.5 and less than or equal to 10.

5. The solar cell according to claim 1 , The sealant layer (14) is a layer constituted by one sealant film. Solar cell.

Citation Information

Patent Citations

  • Organic light emitting device and manufacturing method thereof

    CN103887449A

  • Organic el element

    JP1995169567A

  • Manufacturing method of organic optical device

    JP2012190612A

  • Organic electronic device

    JP2014179266A

  • Organic electroluminescent device and method of manufacturing the same

    JP2014212107A